2019
DOI: 10.14233/ajchem.2019.22128
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Curcumin, Demethoxycurcumin and Bisdemethoxycurcumin Contents in Ethanolic Extract from Ten Curcuma aeruginosa Roxb. Cultivated in West Java, Indonesia

Abstract: Ten accessions of Curcuma aeruginosa Roxb. were grown under the same environment in Bogor, West Java, Indonesia was investigated for curcumin, demethoxycurcumin and bisdemethoxycurcumin contents using HPLC. No significant variations were observed among C. aeruginosa accessions for all the studied compounds. According to the results, curcumin content (mg/100 g extract) varied between 1.08 in accession Kulonprogo to 3.19 in accession Gunung Kidul. The accessions Muara Bungo and Kulonprogo had the highest (1.66) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Therefore, for a commercial scale, this Curcuma aeruginosa Roxb source site should be chosen for future breeding programs that will produce high curcuminoid compounds. 25 The Curcuma aeruginosa Roxb rhizome has three different parts. They are: primary rhizome (PR), secondary rhizome (SR) and tertiary rhizome (TR).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, for a commercial scale, this Curcuma aeruginosa Roxb source site should be chosen for future breeding programs that will produce high curcuminoid compounds. 25 The Curcuma aeruginosa Roxb rhizome has three different parts. They are: primary rhizome (PR), secondary rhizome (SR) and tertiary rhizome (TR).…”
Section: Resultsmentioning
confidence: 99%
“…Secondary metabolites, such as polyphenols influence the pharmacological activities of C. zanthorrhiza and C. aeruginosa rhizomes. Curcuminoid compounds consisting of curcumin, dimethoxy curcumin, and bisdemethoxy curcumin are polyphenolic compounds that have been reported to be present in the rhizomes of C. zanthorrhiza and C. aeruginosa (Nurcholis et al 2016a;Nurcholis et al 2016b;Nurcholis et al 2019;Atun et al 2020;). Many studies have found polyphenols to be effective as antioxidants (Bahukhandi et al 2018;Feduraev et al 2019;Xiang et al 2019), and as a result, evaluating polyphenol in samples will be excellent compared to antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…The phytochemical compounds contained in the C. aeruginosa contribute to its pharmacological properties. C. aeruginosa contains several bioactive compounds such as flavonoid, phenolic acids (Nurcholis et al 2016b), curcumin, demethoxycurcumin and bisdemethoxycurcumin (Nurcholis et al 2019(Nurcholis et al , 2016a, germacrone (Hossain et al 2015;Srivilai et al 2018), isocurcumenol, zederone, curcumenol, dehydrocurdione, zedoarondiol (Suphrom et al 2012), tropolone, eucalyptol, and curcumol (Fitria et al 2019). The reported biological activities of C. aeruginosa and its metabolites include antimicrobial (Akarchariya et al 2017), analgesic effect (Reanmongkol et al 2006), antiandrogenic (Suphrom et al 2012), uterine relaxant effect (Thaina et al 2009), antioxidant (Nurcholis et al 2017), antinociceptive (Hossain et al 2015), hair growth promotor (Pumthong et al 2012), and anticancer (Fitria et al 2019).…”
Section: Introductionmentioning
confidence: 99%